Concrete change: Exploring the effects of scaling up the use of alternative binders to reduce the climate impact from concrete - Escudero Carmona, Santiago (My University, 2019)
This thesis explores the potential of using alternative binders to replace cement clinker on a European scale in order to reduce the carbon dioxide emissions associated with concrete/ cement. Numerous studies highlight the importance of increasing the replacement ratio to meet international environmental goals [1]. However, little advancement has been made with respect to describing how to achieve these replacement goals. This thesis work is focused on estimating the resource base, and the regional availability, of two conventional alternative binders, fly ash and blast furnace slag, in the EU. The availability of fly ash was estimated based on existing coal-fired power plants block net capacity. The blast furnace slag resource base estimated based on the existing and projected capacity of EU blast furnaces. Further, the thesis, through scenario analysis, explore how the availability of alternative binders may change over time as existing capital stock in the power and steel industries are phased out. The scenarios were assessed using simulations from Matlab and further analysed with a software for spatial analysis. The results show that in the short term (5-10 years) it is possible, in most EU regions, to meet the demand for conventional alternate binders. In the long term (10-30 years), however, it will not be possible to fulfil a sufficient replacement in all European regions using only these two alternative binders. These finding confirms the importance of increasing the efforts to develop other measures to reduce the climate impact from concrete and cement, including increased use of lesser-known binders. This study can hopefully encourage further researcher aimed at developing: a better understanding of the availability of other alternative binders, of processing techniques and of means to distribute them, so that the environmental goals in the concrete and cement industries may be achieved.
Keywords: Energi; Hållbar utveckling; Energiteknik; Energy; Sustainable Development; Energy Engineering